Influence of Teachers’ Characteristics on Effective Teaching and Learning of Chemistry in Public Senior Secondary Schools in Etche Local Government Area, Rivers State, Nigeria (Direct Research Journal of Social Science and Educational Studies, 2023)
The study examined the influence of teachers’ character Influence of teachers’ characteristics on effective teaching and learning of chemistry in public secondary schools in Etche local government area, Rivers State, Nigeria. This study adopted a descriptive research survey design. The population of teachers in this local government area was 285 out of which 27 constitutes chemistry teacher and hence this sample size was used for the study as a census. These responded to a researcher self-constructed questionnaire consisting of 12 items on qualification, years of experience and commitment of the teachers using four Likert point scale of SA = Strongly Agree 4, A = Agree 3, D = Disagree 2, SD = Strongly Disagree 1.This scale together with a 2.5 criterion was used to answer the three research questions stated and reliability index 0.76 was reached using Cronbach’s Alpha. The findings revealed that all three variables (qualification, experience and commitment) influence teachers’ effectiveness of teaching and learning in chemistry particularly in public senior secondary schools in Etche local government area in Rivers State, Nigeria. It was therefore recommended among others that government should be ensured that whenever employment exercise is conducted, only those with teaching qualification should be considered no matter the cost.
Keywords: Teachers’ Characteristics; Teaching; Learning; Chemistry; Qualification; Years of Experience; Commitment